2014
DOI: 10.1371/currents.outbreaks.4d41fe5d6c05e9df30ddce33c66d084c
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Impact of Interventions on an Epidemic of Ebola in Sierra Leone and Liberia

Abstract: Background: An Ebola outbreak of unparalleled size is currently affecting several countries in West Africa, and international efforts to control the outbreak are underway. However, the efficacy of these interventions, and their likely impact on an Ebola epidemic of this size, is unknown. Forecasting and simulation of these interventions may inform public health efforts. Methods: We use existing data from Liberia and Sierra Leone to parameterize a mathematical model of Ebola and use this model to forecast the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(94 citation statements)
references
References 7 publications
3
91
0
Order By: Relevance
“…Their study revealed that given a population of 280 million people, it will be possible to prevent 31 million illnesses more by applying the optimal vaccination strategy when compared with the random mass vaccination. Meanwhile Caitlin, et al [16], used existing data from Liberia and Sierra Leone to parameterize a mathematical model of Ebola and used the model to forecast the progression of the epidemic, as well as the efficacy of the several interventions, including increased contact tracing, improved infection-control practices, the use of hypothetical pharmaceutical intervention to improve survival in hospitalized patients. Modeling results showed that increased contact tracing and improved infection control or the combination of the two can have a substantial impact on the number of Ebola cases, but the interventions were not sufficient to halt the progress of the epidemic.…”
Section: Metapopulation and Epidemicsmentioning
confidence: 99%
“…Their study revealed that given a population of 280 million people, it will be possible to prevent 31 million illnesses more by applying the optimal vaccination strategy when compared with the random mass vaccination. Meanwhile Caitlin, et al [16], used existing data from Liberia and Sierra Leone to parameterize a mathematical model of Ebola and used the model to forecast the progression of the epidemic, as well as the efficacy of the several interventions, including increased contact tracing, improved infection-control practices, the use of hypothetical pharmaceutical intervention to improve survival in hospitalized patients. Modeling results showed that increased contact tracing and improved infection control or the combination of the two can have a substantial impact on the number of Ebola cases, but the interventions were not sufficient to halt the progress of the epidemic.…”
Section: Metapopulation and Epidemicsmentioning
confidence: 99%
“…Both, untreated patients in I(t) and hospitalized patients in H(t), may experience one of two outcomes: patients may die, with a chance of infecting others during the resulting funeral F (t) before being removed from this model R(t), or they may recover, at which point they are similarly removed. In system (2.1) the values β I , β H , β F , α, γ, δ, σ, ρ, χ, µ and T are the given positive parameters characterizing the Ebola epidemic ( [12], [14]). …”
Section: (T)i(t)mentioning
confidence: 99%
“…In particular, we use values summarized in Table 1, which were used for modeling of the 2014 Ebola epidemics in Sierra Leone and Liberia ( [7], [14]). Moreover, Table 2 contains the values of the introduced constants.…”
Section: Second We Define the Following Constantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematical models can provide profound logistical, financial, temporal and biological benefits through, for instance, testing potential disease control strategies prior to final design and implementation (Rivers et al, 2014) or to improve current control methods (Turner et al, 2014, Luz et al, 2011. However, valuable models require accurate parameterisations and a reliable understanding of the disease dynamics under investigation and how these can, and do, respond to differential selection pressures.…”
Section: Introductionmentioning
confidence: 99%